Chirality of the biomolecules enhanced its stereospecific action of dihydromyricetin enantiomers. Issue 9 (28th July 2020) - Umair, Muhammad; Jabbar, Saqib; Sultana, Tayyaba; Ayub, Zubaria; Abdelgader, Sheikheldin A.; Xiaoyu, Zhu; Chong, Zhang; Fengxia, Lu; Xiaomei, Bie; Zhaoxin, Lu
Abstract: The present study explores the effect of chirality of the biological macromolecules, its functional aspects, and its interaction with other food components. Dihydromyricetin (DHM) is a natural novel flavonol isolated from the vine tea ( Ampelopsis grossedentata) leaves. However, limited progress in enantiopure separation methods of such compounds hinder in the development of enantiopure functional studies. This study is an attempt to develop a simple, accurate, and sensitive extraction method for the separation of the enantiopure DHM from vine tea leaves. In addition, the identification and purity of the extracted enantiopure (−)‐DHM were further determined by the proton nuclear magnetic resonance ( 1 H‐NMR) and the carbon nuclear magnetic resonance ( 13 C‐NMR). The study further evaluates the antimicrobial activity of isolated (‐)‐DHM in comparison with racemate (+)‐DHM, against selected foodborne pathogens, whereas the action mode of enantiopure (−)‐DHM to increase the integrity and permeability of the bacterial cell membrane was visualized by confocal laser scanning microscopy using green fluorescence nucleic acid dye (SYTO‐9) and propidium iodide (PI). Moreover, the morphological changes in the bacterial cell structure were observed through field emission scanning electron microscope. During analyzing the cell morphology of B. cereus (AS11846), it was confirmed that enantiopure (−)‐DHM could increase the cell permeability that leads to the released of internal cell constituents and, thus, causes cell death. Therefore, the present study provides an insight into the advancement of enantiopure isolation along with its antimicrobial effect which could be served as an effective approach of biosafety. Abstract : The present study explores the effect of chirality of the biological macromolecules and its functional aspects along with the interaction with other major biological macromolecules. Dihydromyricetin (DHM) is a natural novel flavonol isolated from Ampelopsis grossedentata .